Targeting displacement as an indicator of binocular fixation in normal Chinese adults - Lan, Jianqing; Li, Yingan; Pang, Shasha; Zhang, Guanrong; Wu, Dianpeng; Yang, Cheng; Li, Juan; Lin, Junyu; Yang, Xiyang; Li, Zheng; Chu, Hang; Yan, Li; et al. (Frontiers in Neuroscience, 2023)
Purpose: The stability of fixation is crucial for the development of visual function. In this study, we quantify the deviation of visual target during fixational and saccadic tasks using eye-tracking technology, reflecting the control ability and characteristics of fixational displacement among healthy adults in a convenient method. Methods: One hundred healthy participants aged between 18 and 55 years were recruited in the study. All participants underwent a complete ophthalmic assessment. The eye positions in the fixational and saccadic tasks were documented and analyzed by the Tobii eye-tracking system. Participants were grouped by age and gender. Targeting displacement (TD), defined as the average displacement between visual target and the mean of fixation points corresponding to that stimuli, was used to quantitatively observe fixational displacement in the horizontal and vertical directions. Result: There was a strong reproducibility of TD as an indicator of fixation(ICC 0.812 to 0.891,p<0.001). The TD in fixational task was significantly smaller than that of the saccadic task (3.884±0.525 vs. 4.484±0.509, p<0.001) among normal people. Moreover, the difference of TD in the horizontal and vertical meridians was related to the nature of the task: In the fixational task, the TD in horizontal was smaller than that in the vertical (p<0.001), whereas the TD in horizontal was larger than that in vertical in the saccadic task (p=0.003). In the different age and gender groups: There was no significant difference between different gender and age groups in fixational task. However, during the saccadic task, males had smaller TD in the vertical direction than females (4.061±0.495 vs. 4.404±0.484, p=0.002), and the average TD increased with age, mainly in the vertical direction (all p <0.05). The fixation stability decreased significantly in the group over 50-years-old. Conclusion: By reporting the fixational displacement of different genders and ages in fixational and saccadic tasks, as well as different longitude lines among normal people, our study might provide an objective, quantitative and convenient reference index for the evaluation of fixation stability in visual impairment diseases and aging phenomenon of visual function.